The balancing of rotating machinery as non-linear system passing across a resonant region - Nguyen Cao Menh; Tran Duong Tri (Vietnam Journal of Mechanics)
This paper presents a dynamical balancing method for the rotational part of machine as a nonlinear system with the decrease of rotation speed passing across a resonant region. After analyzing the nonlinear system and measurable vibration signals, a suitable procedure of dynamical balance for determining the magnitude and location of imbalance mass is proposed. A program on PC is made to illustrate the obtained procedure. The results of numeric examples show that it can be used well for dynamical balancing analysis.